Impak terapi kerja dalam membantu proses kepulihan klien CCRC - Siti Marziah Zakaria; Juliana Rosmidah Jaafar; Norulhuda Sarnon; Mohd Nasir Selamat; Noordeyana Tambi (Penerbit Universiti Kebangsaan Malaysia, 2020)
Various initiatives and approaches have been taken by the authorities to overcome the problem of drug addiction. Amongst them is a recovery program that uses a recovery approach through work therapy. This program has been launched by the National Anti-Drug Agency of Malaysia (AADK) and implemented at selected CCRC (Cure and Care Rehabilitation Center). In-depth interviews were conducted to six (6) officers that are responsible for guiding and monitoring CCRC trainers in this agricultural project. The transcribed interviews were analyzed by the thematic method of analysis to reveal the key themes of the perception of the officers towards the impacts of the program. The results show that the AADK NBOS3 program has trained the trainee on agricultural projects, enhances efficiency and working capability, training new skills and knowledge, mobilizing attitude change and behavior, leveraging time with quality, and working as a therapy. Thus, the AADK NBOS3 program does not only help trainees to get employed, but also help them to fight drug addiction, improving mental and physical health, preventing cognitive distortion, and changing their mentality and attitude.